1997
DOI: 10.1046/j.1365-2141.1997.1792996.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of minimal residual disease in childhood B‐lineage acute lymphoblastic leukaemia: MRD level at the end of induction is a strong predictive factor of relapse

Abstract: Summary. We prospectively investigated minimal residual disease (MRD) in 51 children with B-lineage acute lymphoblastic leukaemia (ALL) treated according to the Fralle 93 protocol. PCR follow-up was performed in children in morphological and cytogenetic complete remission, provided an immunoglobulin (IgH) gene rearrangement could be detected using FR3/J H amplimers. MRD was studied according to our previously described methodology, with a few modifications including the use of a consensus J H probe to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…25,26 As long as the original rearranged band persisted, which in our hands corresponds to a percentage of at least 1%, no further analysis was performed and contamination was estimated using the value of the peak ( Figure 1). When no signal was observed (corresponding to fewer than 1% malignant cells), a semiquantitative PCR assay was done as described previously [21][22][23] to verify whether MCL cells were still detectable, the sensitivity of the method being 1:10 4 to 1:10 5 ( Figure 2). If residual malignant cells were identified, a LDA, derived from methods described by other authors 27,28 was performed, to better evaluate the number of residual lymphoma cells.…”
Section: Pcr Methodology For Detection Of Residual Malignant Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 As long as the original rearranged band persisted, which in our hands corresponds to a percentage of at least 1%, no further analysis was performed and contamination was estimated using the value of the peak ( Figure 1). When no signal was observed (corresponding to fewer than 1% malignant cells), a semiquantitative PCR assay was done as described previously [21][22][23] to verify whether MCL cells were still detectable, the sensitivity of the method being 1:10 4 to 1:10 5 ( Figure 2). If residual malignant cells were identified, a LDA, derived from methods described by other authors 27,28 was performed, to better evaluate the number of residual lymphoma cells.…”
Section: Pcr Methodology For Detection Of Residual Malignant Cellsmentioning
confidence: 99%
“…21 When amplification could be done with FR3/JH, a probe was directly made according to our previously described method. [21][22][23] In parallel, sequencing of the CDR-III region was performed according to the method used in the laboratory 24 which consists of a direct fluorescence-based methodology with the Prism Sequenase Terminator Single-Stranded DNA Sequencing kit and the ABI 373 apparatus (Applied Biosystems, Foster City, CA, USA). This allowed designing an allele-specific oligomer (ASO) matching the D-N-J sequence for use in a limiting dilution analysis (LDA).…”
Section: Pcr Methodology For Detection Of Residual Malignant Cellsmentioning
confidence: 99%
“…Detection of monoclonality by PCR is also relatively simple and has a level of detection of approximately 10 −3 , a level which virtually all groups agree will identify high-risk patients. [1][2][3][4][5][6][7][8] In early studies of ANZCCSG Study V patients (treated 1985-1989), using material scraped from fixed stained bone marrow smears we reported that detection of monoclonality on day 35, by electrophoresis on standard polyacrylamide gels and subsequent staining, had a positive predictive value for relapse of 37.5%. Using fluorescent consensus primers and Genescan, detection of monoclonality after 20 weeks of treatment was reported to have a positive predictive value of 89% and a sensitivity of 57%.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The hope for the future is that this information may be used to guide and improve treatment. A variety of techniques have been used for studying MRD.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The persistence of high levels of MRD is associated with poor outcome and generally predicts clinical relapse. [4][5][6][7][8][9] A unique pattern of junctional regions of rearranged immunoglobulin heavy chain (IgH) and T cell receptor (TcR) genes has been widely applied as leukemia-or patient-specific targets for Southern blot or polymerase chain reaction (PCR)-based MRD analysis (reviewed in Refs 1,3). The sequences of junctional regions have been determined at diagnosis and sequence-specific oligonucleotides have been designed for further use as patient-specific primers.…”
Section: Introductionmentioning
confidence: 99%